Systematic Literature Review: The Effectiveness of Technology in Education - Muhammad Zaini Abdan; Joy Nashar Utamajaya; Elvin Leander Hadisaputro (Poltanesa, 2025)
Education in the digitalization era has undergone significant changes using technology-based learning media. This research aims to analyze the effectiveness of the application of technology in the context of education in the digital era. This needs to be done because the development of technology is very rapid and makes users, in this case, educators, need to be very careful in choosing effective technology to the needs and conditions that exist in their respective schools. The method used in this research is Systematic Literature Review (SLR) whose data is collected using publish or perish software which then selected thirty related journals to be discussed. Based on the results of the research conducted, it was found that the application of appropriate technology can increase student engagement, concept understanding, and learning motivation, this is indicated by the increase in student scores which experienced a significant increase. The conclusion of the research can be used as a guide for further research and can be used by teachers and educators in choosing the appropriate application of technology. Of course, the application of technology that can be applied to each school or university is different, this is because each technology applied requires different preparations. Each technology discussed in this study has its advantages and disadvantages. This also needs to be considered in the application of technology because the procurement of facilities requires a large amount of money.